Optimization of spray deposition and Tetranychus urticae control with air assisted and electrostatic sprayer - Rezende de Cerqueira, Denise Tourino; Raetano, Carlos Gilberto [UNESP]; Ferreira do Amaral Dal Pogetto, Mario Henrique; Carvalho, Marina Mouzinho [UNESP]; Prado, Evandro Pereira [UNESP]; Almeida Costa, Saulo Italo de [UNESP]; Ferreira Moreira, Caio Alexandre [UNESP] (Univ Sao Paolo, 2017)
Improved spray deposition can be attained by electrostatically charging spray droplets, which increases the attraction of droplets to plants and decreases operator exposure to pesticide and losses to the environment. However, this technique alone is not sufficient to achieve desirable penetration of the spray solution into the crop canopy; thus, air assistance can be added to the electrostatic spraying to further improve spray deposition. This study was conducted to compare different spraying technologies on spray deposition and two-spotted spider mite control in cut chrysanthemum. Treatments included in the study were: conventional TJ 8003 double flat fan nozzles, conventional TXVK-3 hollow cone nozzles, semi-stationary motorized jet launched spray with electrostatic spray system (ESS) and air assistance (AA), and semi-stationary motorized jet launched spray with AA only (no ESS). To evaluate the effect of these spraying technologies on the control of two-spotted spider mite, a control treatment was included that did not receive an acaricide application. The AA spraying technology, with or without ESS, optimized spray deposition and provided satisfactory two-spotted spider mite control up to 4 days after application.
Keywords: application technology; electrostatic spraying; air assisted spraying; flower sector; two-spotted spider mite